Escala para classificação de risco de débito cardíaco diminuído no adulto - Silva, Juliana Mitre da (2020)
Introduction: The concept of decreased cardiac output is found mainly in the nursing and medical fields and is centered on the pumping capacity of the heart. However, due to the similarity of signs and symptoms involving this phenomenon with those of othe